2021
DOI: 10.1007/s42452-021-04266-4
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Malachite green using heterogeneous nanophotocatalysts (NiO/TiO2, CuO/TiO2) under solar and microwave irradiation

Abstract: Heterogeneous photocatalysis is an advanced oxidation process (AOP). This technique is used to degrade a wide range of pollutants in water. In this study, photocatalytic oxidation and mineralization of malachite green in an aqueous suspension containing nickel-based catalysts and copper supported on TiO2 prepared by wet diffusional impregnation was studied using two sources of irradiation: solar and microwave. Photodegradation kinetics were studied according to several parameters, such as catalyst type, dye co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The percentages of photocatalytic activity of the EA600 and EA800 samples towards malachite green dye were compared with those of other photocatalysts such as CuO/TiO 2 , NiO/TiO 2 , CuCo 2 O 4 , chitosan/Ce/ZnO, EDTA/ZnO, Fe(III)-cross-linked alginate–carboxymethyl cellulose, cobalt oxide/citric acid, Dy 2 O 3 /SiO 2 , and lanthanide cerate, as given in Table 1 [ 64 71 ]. Consequently, we can assume that the EA600 and EA800 photocatalysts were highly efficient for the decomposition of the malachite green dye.…”
Section: Resultsmentioning
confidence: 99%
“…The percentages of photocatalytic activity of the EA600 and EA800 samples towards malachite green dye were compared with those of other photocatalysts such as CuO/TiO 2 , NiO/TiO 2 , CuCo 2 O 4 , chitosan/Ce/ZnO, EDTA/ZnO, Fe(III)-cross-linked alginate–carboxymethyl cellulose, cobalt oxide/citric acid, Dy 2 O 3 /SiO 2 , and lanthanide cerate, as given in Table 1 [ 64 71 ]. Consequently, we can assume that the EA600 and EA800 photocatalysts were highly efficient for the decomposition of the malachite green dye.…”
Section: Resultsmentioning
confidence: 99%
“…The COO- group of the carboxylic acid salt could be accountable for the peak at 1385 cm −1 [ 36 ]. As can be seen in the graph below, escin produced distinct peaks caused by its C-H group: asymmetrical peaks at 2924 cm −1 and symmetrical peaks at 2854 cm −1 , respectively; a stretching peak at 1113 cm −1 ; and an out-of-plane bending peak at 955 cm −1 [ 37 , 38 ]. The stretching vibration of the Cu-O and Ti-O bonds also appeared at nearly 710, 594, and 532 cm −1 [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…26 Djebbari et al showed faster solar photodegradation of organic dyes using the NiO/TiO 2 system compared to a single-component system. 27 In this perspective, developing composites of conducting polymers with inorganic materials is one of the important strategies for enhancing the visible-light-driven photodegradation rates of organic dyes. 6,7,28,29 In the photocatalytic process, conducting polymers reduce the recombination of photogenerated electrons and holes, which plays a vital role in dye degradation.…”
Section: Introductionmentioning
confidence: 99%
“…26 Djebbari et al showed faster solar photodegradation of organic dyes using the NiO/TiO 2 system compared to a single-component system. 27…”
Section: Introductionmentioning
confidence: 99%